Developing Ipoh homemade chocolate e-commerce website using user centered design approach / Mariani Mohd Dahlan - Mohd Dahlan, Mariani (2012)
Currently, Ipoh Homemade Chocolate is using BlogSpot Website as a platform to promote homemade chocolate in the internet but there are some problems with this social website. There are three (3) problems in using BlogSpot Website as a platform for e-Commerce business which are limited amount of payment method, limited space for handling more than hundred products on a single database and also eBlog does not offer accounting and proper report for any purchase from the customers. Therefore, the one of objective of this project is to develop e-Commerce website for Ipoh Homemade Chocolate using User Centered Design approach. The data required to conduct this project was acquired using four (4) research instruments; the questionnaire, interview, checklist and direct user observation in order to address all the user requirements and needs during developing the website. At the end of this paper, some recommendations are presented regarding Ipoh Homemade Chocolate e-Commerce website that can be taken into account when redeveloping the website in the future.